Desain Kontrol Beban Elektronik pada Pembangkit Listrik Tenaga Mikrohidro - Effendy, Machmud (Jurnal Semesta Teknika, 2009)
Due to its lower cost and quicker response in compassion with governor, electronic load control (ELC) has been widely used to replace governor in microhydro power plant. It has lower price and quicker response than governor. The synchronous generator used in microhydro power plant produces stable voltage, because it has been controlled by an AVR (automatic voltage regulator. If consumer loads changes, the frequency not the voltage of the electrical wave will change. Therefore, ELC is used to stabilize the electrical wave frequency and detect the change of consumer load to be transferred to ballast load. This ELC uses frequency censor to detect the change of consumer load. Frequency censor proceeses linearity level to the change of voltage which equals to R2= 0.97. The use of ELC causes the generator voltage is approximately 220,3V to 224,4V with percentage of voltage unbalance 0,56% and the geneator frequency is 49,5Hz to 50,1Hz with percentage of frequency unbalance 0,41%.